Analysis of the Effect of Using Concrete Mattresses on Subsea Pipelines - Risal, Risal; Sade, Juswan; Assidiq, Fuad Mahfud (Maritime Park: Journal of Maritime Technology and Society, 2024)
This Leaks in oil and gas pipes under the sea will cause pollution and threaten the ecosystem in the sea. Damage to underwater pipes caused by anchors has quite a large percentage, therefore good prevention efforts are needed so that leaks do not occur which have a negative impact on environment and economy. The aim of this research is to find out how the strength compares between pipes that use protective concrete mattresses and pipes without protective concrete mattresses when hit by ship anchors. This research uses explicit dynamic simulation using Finite Element Method software. Based on explicit dynamic analysis, deformation values ​​and equivalent stress values ​​are obtained after being hit by an anchor at a speed of 5,491 m/s. For unprotected pipes experiencing significant damage, when viewed from the deformation values ​​obtained, namely amounted to 0.143 m, while for the pipe model with protection the deformation value obtained was 0.0769 m. For pipes without protection and pipes that use protection with a thickness of 0.15 m, the deformation value is both above the maximum value that has been determined, namely 10% of the diameter value and when viewed from the equivalent stress value, for pipes without protection the equivalent stress value is obtained. namely 1,150 MPa, while the pipe that uses a protector is 240 MPa, the equivalent stress value obtained by the pipe using a protector is below 780 MPa, which means that the use of pipe protectors is quite effective in reducing damage that occurs to the pipe.